Interplay Between Premature Ejaculation and Erectile Dysfunction: A Systematic Review and Meta‐Analysis. (9th November 2015) - Corona, Giovanni; Rastrelli, Giulia; Limoncin, Erika; Sforza, Alessandra; Jannini, Emmanuele A.; Maggi, Mario
Abstract: Introduction: The specific determinants and underlying factors linking erectile dysfunction (ED) and premature ejaculation (PE) have yet to be clearly identified. Aim: The aim of this study was to review and meta‐analyze all available data regarding the link between ED and PE. Methods: An extensive Medline Embase and Cochrane search was performed including the following words: "premature ejaculation" and "erectile dysfunction". Main Outcome Measures: All observational trials comparing the risk of ED in relation to PE were included. Data extraction was performed independently by two of the authors (G.R, G.C.), and conflicts resolved by the third investigator (M.M.). Results: Out of 474 retrieved articles, 18 were included in the study for a total of 57, 229 patients, of which 12, 144 (21.2%) had PE. The presence of PE, however defined, was associated with a significant increase in ED risk (odds ratio: 3.68[2.61;5.18]; P  < 0.0001). Meta‐regression analysis showed that the risk of ED in PE subjects was higher in older individuals as well as in those with a lower level of education and in those who reported a stable relationship less frequently. In addition, subjects with PE and ED more often reported anxiety and depressive symptoms and a lower prevalence of organic associated morbidities, including diabetes mellitus, hypertension and dyslipidemia. All the latter associations were confirmed even after adjustment for age. Finally the risk of PE‐related ED increased with the increased proportion of acquired ejaculatory problems (adj r  = 0.414; P  < 0.0001 after the adjustment for age). Conclusions: In conclusion, the present data showed that ED and PE are not distinctly separate entities, but should be considered from a dimensional point of view. Understanding this dimensional perspective might help sexual health care professionals in providing the most appropriate therapeutic approach to realistically increase patient related outcomes in sexual medicine.Corona G, Rastrelli G, Limoncin E, Sforza A, Jannini EA, and Maggi M. The interplay between premature ejaculation and erectile dysfunction: A systematic review and meta‐analysis. J Sex Med 2015;12:2291–2300.